2016
DOI: 10.4103/1305-7456.178305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whitening dentifrices on the surface roughness of a nanohybrid composite resin

Abstract: Objectives:The present study verified the influence of whitening dentifrices on the surface roughness of a nanohybrid composite resin.Materials and Methods:Thirty-two specimens were prepared with Filtek™ Z350 XT (3M/ESPE) and randomly divided into four groups (n = 08) that were subjected to brushing simulation equivalent to the period of 1 month. The groups assessed were a control group with distilled water (G1), Colgate Total 12 Professional Clean (G2), Sensodyne Extra Whitener Extra Fresh (G3), and Colgate L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 26 publications
3
26
0
1
Order By: Relevance
“…On the other hand, it was found that the shrinkage of ormocer was equal to that of hybrid composites despite having less filler content. The authors [14] attributed their findings to the difference in the resin matrix of ormocer [11]. As a result, it was suggested that the advantages of ormocers include amongst others: low shrinkage (1.97 vol%) , high abrasion resistance (compressive strength of 410 Mpa), biocompatibility, protection against caries, does not liberate any residual monomer after polymerization and has a better manipulation [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it was found that the shrinkage of ormocer was equal to that of hybrid composites despite having less filler content. The authors [14] attributed their findings to the difference in the resin matrix of ormocer [11]. As a result, it was suggested that the advantages of ormocers include amongst others: low shrinkage (1.97 vol%) , high abrasion resistance (compressive strength of 410 Mpa), biocompatibility, protection against caries, does not liberate any residual monomer after polymerization and has a better manipulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was suggested that the advantages of ormocers include amongst others: low shrinkage (1.97 vol%) , high abrasion resistance (compressive strength of 410 Mpa), biocompatibility, protection against caries, does not liberate any residual monomer after polymerization and has a better manipulation [12]. Ormocer materials have multiple indications in dentistry such as direct restoration for all types of cavities, cosmetic veneers, protective sealant for child teeth, protective varnish as caries prophylaxis and as orthodontic bonding adhesive [13,14]. It is believed that the ormocer material is an excellent option for posterior restorations.…”
Section: Introductionmentioning
confidence: 99%
“…The complex association of the various aforementioned factors is not easily reproducible in an in vitro setting. Although the study of each of these factors on the degradation of resin composites has provided valuable scientific evidence, it has also generated contradictions . Tooth brushing increases resin composite roughness, which negatively affects optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study of each of these factors on the degradation of resin composites has provided valuable scientific evidence, it has also generated contradictions. 3,4,9,13,14 Tooth brushing increases resin composite roughness, 2,3 which negatively affects optical properties. On the other hand, tooth brushing has also been associated with reduced retention of extrinsic pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Acceptable performance of esthetic restorative materials is dependent on their resistance to degradation in the oral environment (Asmussen & Hansen 1986). Among the contributing factors are abrasion resulting from mastication, attrition, corrosion, erosion, and effects of hygiene procedures (Asmussen & Hansen 1986;Schmitt et al 2011;da Rosa et al 2016). Tooth brushing is an oral hygiene method that can increase the surface roughness of resin composites (Kamonkhantikul et al…”
Section: Introductionmentioning
confidence: 99%